Pengaruh Media Let’s Read Berbasis E-Book Terhadap Minat Baca Peserta Didik Sekolah Dasar - Pratama, Farhan Iqbal; Kuncoro, Wahyu Ringgit; Supriyadi, Supriyadi; Hermawan, Jody Setya (Universitas Hamzanwadi, 2024)
“The objective of this investigation was to ascertain the impact of e-book-based Let's Read media on the level of student interest in reading. The sample for this research consisted of 24 students from class IV B SD Negeri 2 Metro Selatan. This study employs a quantitative approach in conjunction with a descriptive methodology. The data were analyzed using descriptive statistical methods, which involved calculating the average increase in data processing results using a Likert scale. The results of this study indicate that 68.55% of the respondents agreed that the use of Let's Read media can increase interest in reading, as indicated by the questionnaire that was distributed. It has been determined that the reading interest of students in class IV B SD Negeri 2 Metro Selatan is influenced by e-book-based Let's Read media”.